Thermogravimetric study of the reduction of copper slag by biomass - Zuo, Zongliang; Yu, Qingbo; Wei, Mengqi; Xie, Huaqing; Duan, Wenjun; Wang, Kun; Qin, Qin (Journal of thermal analysis and calorimetry, 2016)
The utilization of copper slag is an attractive option of iron resource. However, extra energy consumption is required and contributes to greenhouse gases. In this paper, biomass was introduced as a new kind of reductant for the reduction of copper slag to decrease the energy consumption. The reduction kinetics and reduction characteristics of three kinds of biomasses were studied by thermogravimetric analyzer (TG). The TG curves showed the reduction reaction of copper slag and biomass could be divided into three stages during heating process: drying and pyrolysis of biomass process (1100 K). Pine sawdust showed the best reducing property and the reduction ratios of pine sawdust, corncob and straw reached to 80.6, 76.1, and 60.0 %, respectively, when the mass ratio of biomass/slag was 2:1. As the additive, CaO had promotion effects on the reduction reaction. With the increase in CaO addition, the reduction ratio of copper slag increased firstly and reached a peak at CaO/slag was 0.3:1 and then it declined due to the changes of slag viscosity. By kinetics analysis, the reduction reaction confirmed well with shrinking core model (R1). The activation energy of reactions was affected by the addition of biomass and heating rate in experiments. With the increase in the addition of biomass, the activation energy of reduction reaction increased gradually; with the increase in heating rate, the activation energy of reduction reaction decreased.